Participation of Gapoktan Sidomakmur Members in Purworation Village, Purwosari Subdistrict - Hendriawan, Jemi; Suminah, Suminah; Suwarto, Suwarto (SERUNAI, 2023)
Community or member participation is one of the important aspects in the running of an institution or organisation. This research was conducted to analyse the participation of Gapoktan Sido Makmur members. It is a research that uses qualitative approach. Determination of informants was done by purposive sampling with key informants and snowball sampling techniques, a total of 12 informants. Data validity used triangulation as a method to validate the data. The discussion was conducted with reference to the theory of Totok Mardikanto and Subianto. The results show that the participation of Gapoktan Sidomakmur members is divided into four types, namely decision-making, implementation of activities, monitoring and evaluation of activities, and utilisation of development results. Participation in decision-making is still low due to lack of understanding, ineffective communication, and lack of awareness among members. In contrast, participation in the implementation of development activities is high due to members' commitment and awareness of the benefits. However, participation in monitoring and evaluation is still low due to a lack of understanding of the importance of these activities. On the other hand, participation in utilisation of development outcomes is high, indicating members' awareness and commitment to engage in economic and social activities resulting from development.